Hubungan Dukungan Sosial Terhadap Kecemasan Pasien Polycycstic Ovary Syndrome (PCOS) - Deninta Silvia Hanani; Anis Ardiyanti; Nella Vallen Ika P (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Background: PCOS is a problem experienced by females due to interrupted hormones until the reproduction process is interrupted. This matter leads to anxiety and requires social support. Objective: This research determined the correlation between social support and the anxiety of polycystic ovary syndrome patients. Research design: this descriptive quantitative took 48 respondents as the samples. Research results: most respondents were in early adulthood (52.1%). Most respondents graduated from high education (54.25). They had high social support (89.4%) and got mild anxiety (79.2%). The Spearman rank test obtained a p-value of 0.000 lower than 0.05, indicating the correlation between social support and anxiety levels of PCOS patients. Conclusion: High social support could relieve the patient's anxiety. Suggestion: The researcher expects future researchers will apply qualitative design to reveal the new PCOS patients' knowledge.